Penghapusan Kekerasan Seksual malam Melindungi Korban Pelecehan Seksual Secara Verbal (Catcalling) di Indonesia - Anak Agung Ayu Wulan Pramesti Puja Dewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
Catcalling is a type of verbal sexual harassment in public spaces that often occurs without the victim realizing it. The lack of clarity on the legal basis for handling catcalling in the settlement of cases has resulted in victims being afraid to report to the authorities. The purposes of this study are to analyze the legal regulation of sexual violence in protecting victims of verbal sexual harassment in Indonesia and the form of eliminating sexual violence in protecting victims of verbal sexual harassment (catcalling). This research method is normative legal research with a statutory approach, a conceptual approach, and a case approach. The technique of collecting legal materials used in this paper is through documentation study techniques. The sources of law used are primary, secondary, and tertiary sources of law. After the data is collected, then it is analyzed systematically. The results of the study reveal that there is no statutory regulation that explicitly regulates catcalling. However, catcalling can be classified as a criminal act because it has fulfilled the elements, principles of criminal law, and the values ​​contained in Article 218 of the Criminal Code and Article 9 in conjunction with Article 35 of Law Number 44 of 2008 concerning pornography. The form of eliminating sexual violence in protecting victims of catcalling requires a special legal policy that contains the formulation of morals, basic values ​​and theories that are correlated with legal policies.